Fertility sparing in cancer patients. Issue 4 (July 2012) - Bouchlariotou, Sofia; Tsikouras, Panagiotis; Benjamin, Roesing; Neulen, Josef
Abstract: Infertility can arise as a consequence of treatment of oncological conditions. As cancer survival rates continue to improve, many women will face infertility after successful treatment of their malignant diseases. This review summarizes the current state of different fertility preservation options in these patients. This review will discuss the premature ovarian failure and other adverse reproductive outcomes in female patients who receive chemotherapy and radiation. In addition, cancer-specific fertility preservation methods are presented. Embryo cryopreservation is a well established technique to preserve fertility. However, it requires delaying cancer treatment for two to six weeks and a partner or willingness to use donor sperm. When these criteria cannot be met, more experimental options include oocyte cryopreservation for later IVF and ovarian tissue cryopreservation. In-vitro maturation is a promising technology and can be applied in combination with oocyte or ovarian tissue cryopreservation. Ovarian transposition remains the standard option for women undergoing pelvic radiation. Lastly, the efficacy of GnRH analoga in ovarian protection during chemotherapy has still not been proved. As fertility preservation choices include both established and experimental methods, a highly individualized approach is required in the management of patients looking for fertility preservation options.